2000
DOI: 10.2486/indhealth.38.356
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations to Determine the Most Appropriate Welding and Ventilation Conditions in Small Enclosed Workspace.

Abstract: In order to improve arc welding work in a small enclosed workspace, numerical simulations were conducted to find the most appropriate welding and ventilation conditions, such as welding currents, hood position and flow rates with no blowhole formation. In the simulations, distributions of airflow vectors and fume concentrations were calculated for two hood opening positions: one faced a welder's breathing zone, the other a contaminant source. As a result it was predicted that a hood opening facing a breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, a good CFD model, which typically contains some empirical features, captures the relevant physics (2) of contaminant transport, generating plausible concentration fields that provide meaningful comparisons to simple deterministic models. As other researchers continue to demonstrate good agreement between measured concentration fields and fields simulated using CFD, (3,4) the potential of CFD as a means of simple model evaluation becomes evident. The effectiveness of this approach stems from the relative ease with which variables such as room shape and supply air inlet velocity can be changed and detailed spatial concentration information obtained.…”
mentioning
confidence: 91%
“…However, a good CFD model, which typically contains some empirical features, captures the relevant physics (2) of contaminant transport, generating plausible concentration fields that provide meaningful comparisons to simple deterministic models. As other researchers continue to demonstrate good agreement between measured concentration fields and fields simulated using CFD, (3,4) the potential of CFD as a means of simple model evaluation becomes evident. The effectiveness of this approach stems from the relative ease with which variables such as room shape and supply air inlet velocity can be changed and detailed spatial concentration information obtained.…”
mentioning
confidence: 91%
“…Many studies have concluded that particles tend to follow the airflow when moving because of small diameters. [37][38][39][40][41] Therefore, the turbulence effect of fluid can significantly influence particles' motion trajectory through momentum transfer. For the motion of particles in turbulence, Salmanzadeh et al 42 have studied the turbulent thermal plume on particle concentrations in the breathing zone and entrainment of particles emitted from different sources near the floor.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of gas shielded welding is frequently performed in enclosed compartments and rooms such as in shipbuilding industries where the welder has exposure to a high concentration of fumes [7]. Gomes et al did assessments of airborne ultrafine particles generated from tungsten inert gas, metal active gas, and friction stir welding, and found that all these processes emitted significant concentrations of ultrafine particles which were deposited in the lungs of exposed workers [8,9].…”
Section: Introductionmentioning
confidence: 99%